1960
DOI: 10.1136/ard.19.4.318
|View full text |Cite
|
Sign up to set email alerts
|

Sulphate (35SO4) Uptake by Chondrocytes in Relation to Histological Changes in Osteo-Arthritic Human Articular Cartilage

Abstract: Quantitative studies of sulphate uptake by the cells of human cartilage (McElligott and Collins, 1960) have shown that chondrocyte activity increases in articular cartilage as age advances, while it decreases in costal cartilage. A considerably enhanced activity of articular over costal cartilage cells was recorded in cases where there was nakedeye evidence of destruction and fibrillation of the articular cartilage. We postulated a possible relationship between the increased sulphate utilization of ageing arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
107
0
1

Year Published

1964
1964
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(117 citation statements)
references
References 15 publications
7
107
0
1
Order By: Relevance
“…The histologic results presented are consistent with those found in numerous studies of human and experimental OA (20)(21)(22)(23)(24)(25)(26)(27). They show a general loss of intercellular matrix staining, but persistence of a strong pericellular reaction around most chondrocytes and cell clusters.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The histologic results presented are consistent with those found in numerous studies of human and experimental OA (20)(21)(22)(23)(24)(25)(26)(27). They show a general loss of intercellular matrix staining, but persistence of a strong pericellular reaction around most chondrocytes and cell clusters.…”
Section: Discussionsupporting
confidence: 89%
“…However, despite their routine description in published reports, relatively little is known of their formation or function. Previous studies have demonstrated enhanced sulfate incorporation by chondrocyte clusters in fibrillated patellae, and this was related to the rate of chondrocyte proliferation (21,44). While chondrocytes in normal cartilage are generally considered to be mitotically dormant, convincing metabolic (35,47,50) and autoradiographic (45,46,48,49) evidence has shown that chondrocytes can switch to a reactive mitotic proliferation under traumatic or degenerative conditions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…DISCUSSION An in vitro adult rabbit articular cartilage organ model has been reported. Dziewiatkowski and others (1)(2)(3)(4)(5)13,14) have clearly shown that 90% plus of s 5 S 0 , is incorporated into glycosaminoglycans and that its incorporation is related to the rate of synthesis. By utilizing this technique we have shown that the articular cartilage slices and floating plugs have the property of a constant rate of 35S0, incorporation into glycosaminoglycans from day 7 to day 14.…”
Section: Thementioning
confidence: 99%